Sanctioning in Myanmar : do sanctions work? - Myo Min. (2010)
This paper studies the effectiveness of western sanctions against Myanmar in the triumph of democratization. The U.S and EU governments have imposed sanctions against Myanmar since 1988 uprising. However, these sanctions have not worked effectively to get the desired outcomes of regime change into democratic country. Therefore, the objective of this paper is to analyze 'why the western's sanctions do not work effectively?' The dissertation argues that western sanctions against Myanmar do not work effectively because there is no full cooperation from the Asian countries such as China, India and ASEAN countries. These Asian countries have practiced the 'constructive engagement' with Myanmar military regime. Thus, the western' sanctions policy and constructive engagement policy from Asian countries cancel each other. Moreover, Myanmar can access the international market easily because of its natural resources such as teak, gems and natural gas. In addition, the military government has already established their regime strongly and there is no cohesion among the opposition groups. Hence, this paper finally highlights that the western's sanctions against Myanmar do not work effectively to transform the country into democratic regime.